Strict liability for infected blood transfusion - Amin, Naemah (Law Centre, Ahmad Ibrahim Kulliyyah of Laws, 2003)
The paper analyses the possibility of imposing strict liability for injury caused by infected or defective blood transfusion under Part X of the Consumer Protection Act 1999.